Halal Knowledge, Religiosity, and Halal Awareness: Determinants of Generation Z Consumers Purchase Decision - Sefni Novita Sari; Dessi Susanti (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: Recently, the demand for halal cosmetic goods has significantly expanded, particularly among Generation Z customers in West Sumatera, Indonesia. Notwithstanding their robust religious base, the understanding of halal cosmetics is still fairly confined. Purpose: This study analyze the impact of halal knowledge and religiosity on consumer behavior, with halal awareness as a mediating variable. Method: This research used a quantitative research design with a survey approach. The sampling technique applied purposive sampling based on certain criteria in accordance with the research objectives. The number of respondents collected was 384 people. Data were analyzed using Structural Equation Modeling (SEM). Findings: Halal knowledge and religiosity positively influence halal awareness, significantly impacting consumer behavior. Additionally, halal awareness mediates the junction of halal knowledge, religiosity, and consumer behavior. Conclusions: The results highlight the need to educate Generation Z about halal certification and criteria to raise their knowledge and propensity toward halal cosmetics. Research implications: This study provides important information for halal cosmetics producers, marketers, and legislators to help them develop effective strategies to reach young Muslim customers. Price sensitivity, brand loyalty, and the impact of online marketing on halal consumer behavior are further topics that should be explored in future studies.